The Standards of Proof in Medical Malpractice Cases - Cek, Nina (Medicine, Law & Society, 2020)
The article examines the procedural aspect of medical malpractice cases. It focuses on the differences in standards of proof by first explaining the characteristics of the Slovenian legal system and then comparing it with German and English legal systems. The author sheds light on the approach of the EU court on the question of the responsibility of the manufacturer for the product (vaccine) and suggests the direction to use a broader framework for the evaluation of evidence and presumptions. Given the disclosed problems of proving through the help of a medical expert, the article emphasizes the importance of respect for human rights in civil proceedings. Particular emphasis is also placed on no-fault systems and the question is raised of how the introduction of such a system into the Slovenian legal system would affect the perceived problem of proving a medical error and informed consent omission.